Eliot Freidson's sociology of professions: an interpretation for Health and Nursing - Maria Lígia dos Reis Bellaguarda; Maria Itayra Padilha; Sioban Nelson
ABSTRACT Objectives: to analyze theoretical conceptions of Eliot Freidson's Sociology of Professions scoped on health and nursing professions. Methods: Eight nurses were interviewed, all involved in the development of the professional Council on the timeframe from 1975 to 1986. Documental resources were Laws, Ordinances, Resolutions, Reports, Meeting Minutes and Public Deeds. Information was organized as from literature and Eliot Freidson's conceptions, and thematic content analysis was carried out. Results: the concepts authored by Eliot Freidson allowed for the development of a concept chart that portrays the nursing profession and that may be expanded for the other occupations in the health field, in consonance with professional organization in the country. Final Considerations: Eliot Freidson's framework, in interpretation for nursing, consolidates the profession with relative autonomy, expertise by Nursing Care Systematization and credentialism by professional normalizations.